Diagnosis of Ectopic Thyroid Gland by 99mTc Scan : A Case Report - Jahan, Nafisa; Sharmin, Ferdous; Jahan, Nusrat; -, Nadiruzzaman; Ahmad, SM Mesbah Uddin (Bangladesh Journal of Nuclear Medicine, 2018)
Ectopic thyroid is an uncommon entity. Its occurrence in children is rare. Most of the patients present with mid neck swelling that may be confused with other midline pathology. Sometimes it may be the only functioning thyroid tissue present in the body as reported in this case. Proper diagnosis is required for the management of the patient. Radionuclide scan and high resolution ultrasonography plays an important role in diagnosis and further management of the patient with ectopic thyroid gland. Bangladesh J. Nuclear Med. 20(2): 151-154, July 2017